2016
DOI: 10.1089/scd.2015.0248
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Can Effectively Differentiate into Multiple Functional Lymphocyte Lineages In Vivo with Negligible Bias

Abstract: Lymphohematopoietic stem cells (L-HSCs) generated from self-somatic cell-derived induced pluripotent stem cells (iPSCs) are a potential source of cells for the treatment of hematological disorders. However, the generation of truly functional L-HSCs from iPSCs has yet to be achieved. Thus, whether iPSCs have the inherent potential to generate a normal differentiated phenotype and functional population of multiple lineages of terminally differentiated lymphocytes needs to be assessed. Here, we used tetraploid em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Genotyping revealed that 5 of 20 chimeras (40%) were derived from Fgf10 Ex1 mut /Ex3 mut embryos (Tables 1 and S2). The Fgf10 Ex1 mut /Ex3 mut chimeras exhibited a significant body-weight gain compared with Fgf10 wild-type and Fgf10 Ex1 mut /Ex3 mut mice, whereas no significant difference was observed between the groups of chimeric neonates (Figure S2B), which is consistent with previous observations (Lan et al, 2016;Mori et al, 2019). Macroscopic analysis and micro-CT confirmed the existence of a lung in the thoracic cavity of the Fgf10 Ex1 mut /Ex3 mut chimeras (Figures 2A and 2D; continuous CT images in Video 3).…”
Section: Generation Of Lungs In Apneumic Fgf10 Ex1 Mut /Ex3 Mut Micesupporting
confidence: 92%
“…Genotyping revealed that 5 of 20 chimeras (40%) were derived from Fgf10 Ex1 mut /Ex3 mut embryos (Tables 1 and S2). The Fgf10 Ex1 mut /Ex3 mut chimeras exhibited a significant body-weight gain compared with Fgf10 wild-type and Fgf10 Ex1 mut /Ex3 mut mice, whereas no significant difference was observed between the groups of chimeric neonates (Figure S2B), which is consistent with previous observations (Lan et al, 2016;Mori et al, 2019). Macroscopic analysis and micro-CT confirmed the existence of a lung in the thoracic cavity of the Fgf10 Ex1 mut /Ex3 mut chimeras (Figures 2A and 2D; continuous CT images in Video 3).…”
Section: Generation Of Lungs In Apneumic Fgf10 Ex1 Mut /Ex3 Mut Micesupporting
confidence: 92%
“…Manufacturing of clinical-grade NK cells from either embryonic (ES) or induced pluripotent stem (iPS) cells nowadays appear as a futuristic option, although preclinical demonstrations that NK cells can be differentiated from these sources of pluripotent stem cells were already published (5456). For iPS cells, several factors affect the pluripotency and differentiation abilities of reprogramed cells: the choice of target donor somatic cell type and the reprograming protocol, including the nature and combination of genes as well as the method used to deliver transcription factors into somatic cells (57).…”
Section: Factors Affecting Nk Cell Product Manufacturingmentioning
confidence: 99%
“…Thus, an altered approach is desired which can offer identical environment as human cells and iPSCs seem like an amenable substitute with plethora of advantages. iPSCs do not require multiple proliferation and their derivatives are functional after transplantation in vitro as well as in vivo [ 39 , 40 , 41 , 42 , 43 ]. Hence iPSCs are used in therapeutics for disease modelling, drug screening and regenerative medicine.…”
Section: Applications Of Ipscsmentioning
confidence: 99%